Electron microscope based X-ray microanalysis on bioaccumulation of heavy metals and neural degeneration in mudskipper [Pseudapocryptes lanceolatus]. Issue 4 (December 2016) - Sarkar, Swaraj K.; De, Subrata K.
Abstract: The bioaccumulation of heavy metals and its probable cytological consequences in ciliated olfactory sensory receptor neuron (OSN) of two different groups of Pseudapocryptes lanceolatus has been studied using X-ray microanalysis in transmission electron microscopy (TEM-EDX) [i.e., Group I, collected near Kanchrapara (22.56°N 88.26°E) and Group II, collected near Tribeni (22.99°N 88.40°E) of West Bengal, India]. The ciliated OSN is a bipolar neuron and possesses a prolonged dendron with four to six cilia at the olfactory knob, perikaryon, and axon. Excess accumulation of copper (94.50%) and iron (83.81%) was noted under TEM-EDX in the cytoplasm of the olfactory knob as well as nucleoplasm of ciliated OSNs in P. lanceolatus (Group II). The degenerating ciliated OSNs show distinct features of lysis of the plasma membrane at the olfactory knob, disintegration of cytoskeletal structures in perinuclear cytoplasm and axoplasm, and fragmented chromatin fibers with granules (diameter, 20–30 nm) in the nucleoplasm. Crowding of acetylcholinesterase-positive vesicles (diameter:, 30–40 nm) at the terminal part of the axoplasm was related to accumulation of heavy metals in degenerating ciliated OSNs of P. lanceolatus (Group II). The recorded concentrations of heavy metals in the same organ among different groups of P. lanceolatus in varying geographical areas indicates the stress of concerned environmental health. This ultrastructural interpretation on the fish ciliated OSN is a prerequisite for monitoring environmental health as well as metallobiology of several neurodegenerative disorders in fish caused by bioaccumulation of heavy metals.